MSCT-semiotics of muscles in chronic osteomyelitis of the femur and lower leg - Galina V. Diachkova; Alexander L. Shastov; Konstantin A. Diachkov; Nikolai M. Kliushin; Vyacheslav D. Gayuk; Ilya V. Sutyagin; Tat'iana A. Larionova (Гений oртопедии, 2022)
Introduction It is known that the function and structure of the muscles of the thigh and lower leg are closely related to the function of the lower limb, which is impaired to one degree or another in all patients with chronic osteomyelitis. However, the nature of structural changes in the muscles, which, in turn, affect the condition of the bones, has not been well studied. Purpose of the work To study the features of changes in the muscles of the thigh and lower leg in patients with chronic osteomyelitis according to MSCT data. Material and methods The study is retrospective conducted at a single centre of Evidence level IV. Multislice computed tomography (MSCT) was used in 112 patients with chronic osteomyelitis of long bones of the lower extremities to study the radiological morphology of the muscles of the thigh and lower leg, including density, muscle belly area, and anatomical features. Twenty patients had chronic osteomyelitis in the area of transosseous elements (pins). The mean age of the patients was 48.5 ± 9.8 years. Males prevailed among the patients (87.5 %). The cause of osteomyelitis in 107 cases was trauma or surgery, five patients had consequences of hematogenous osteomyelitis. Results The results of the study showed that the muscles of the thigh and lower leg in patients with chronic osteomyelitis have pronounced dystrophic changes. In 89.4 % of patients, they were manifested by an increase in the density of the anterior tibial muscle, long extensor of the toes (84.7 %), peroneal muscles (78.5 %) and a decrease in the density of the head of the gastrocnemius muscle (91.3 %). In 10.6 % of the patients, there was a decrease in the density of the anterior tibial muscle, the long extensor of the fingers. In all patients with chronic osteomyelitis of the femur, the density of the muscles of the anterior and posterior groups was reduced, except for the musculus vastus intermedius of the thigh that was characterized by fibrotic changes with an increase in density. Conclusion The data obtained indicate that radiological morphological changes in muscles occur in all patients with chronic osteomyelitis of the femur and lower leg. The most pronounced alterations in the architectonics were in the anterior tibial and gastrocnemius muscles, and the intermediate broad muscle of the thigh.